A hybrid KB-AHP-GAP Analysis for the Performance Measurement System ( PMS ) in a manufacturing environment - Wibisono, Dermawan (Jurnal Manajemen Teknologi, 2003)
Designing and implementing PMS in an integral part of management control systems. To be effective, performance measures need to reflect the changes in competitiveness. However, traditional PMS is criticized for being obsolete, irrelevant to managerial decision making, unrelated to strategic objectives and detrimental to organizational improvements. Given the shortcomings of traditional PMS, there is need for a new framework that can lead to the design of a PMS that balances short-term and long-term measures, internal and external measures, and financial and operational measures. This paper presents on designing and managing performance of a manufacturing unit from the corporate level to the shop floor level. It seeks to frame work of PMS specific to a manufacturing environment, and implementation of Knowledge Based (KB) systems, Gauging Absences of Pre-requisite (GAP) analysis and Analytic Hierarcy Process (AHP) approach in an integrated PMS.Keywords:Â Performance Measurement System (PMS), Knowledge Based (KB), Analytic Hierarcy Process (AHP), GAP analysis, Manufacturing